Efficacy of combined use of a stent retriever and aspiration catheter in mechanical thrombectomy for acute ischemic stroke. (20th September 2021) - Okuda, Tomohiro; Arimura, Koichi; Matsuo, Ryu; Tokunaga, So; Hara, Kenta; Yamaguchi, Shinya; Yoshida, Hidenori; Kurogi, Ryota; Kameda, Katsuharu; Ito, Osamu; Tsumoto, Tomoyuki; Iihara, Koji; et al.
Abstract : Background: The efficacy of combined stent retriever (SR) and aspiration catheter (AC; combined technique: CBT) use for acute ischemic stroke (AIS) is unclear. We investigated the safety and efficacy of single-unit CBT (SCBT)—retrieving the thrombus as a single unit with SR and AC into the guide catheter—compared with single use of either SR or contact aspiration (CA). Methods: We analysed 763 consecutive patients who underwent mechanical thrombectomy for AIS between January 2013 and January 2020, at six comprehensive stroke centers. Patients were divided into SCBT and single device (SR/CA) groups. The successful recanalization with first pass (SRFP) and other procedural outcomes were compared between groups. Results: Overall, 240 SCBT and 301 SR/CA (SR 128, CA 173) patients were analyzed. SRFP (modified Thrombolysis In Cerebral Infarction (mTICI) ≥2c, 43.3% vs 27.9%, p<0.001; mTICI 3, 35.8% vs 25.5%, p=0.009) and final mTICI ≥2b recanalization (89.1% vs 82.0%, p=0.020) rates were significantly higher, puncture-to-reperfusion time was shorter (median (IQR) 43 (31.5–69) vs 55 (38–82.2) min, p<0.001), and the number of passes were fewer (mean±SD 1.72±0.92 vs 1.99±1.01, p<0.001) in the SCBT group. Procedural complications were similar between the groups. In subgroup analysis, SCBT was more effective in women, cardioembolic stroke patients, and internal carotid artery and M2 occlusions. Conclusions: SCBT increases the SRFP rate and shortens the puncture-to-reperfusion time without increasing procedural complications.